2012
DOI: 10.3892/mmr.2015.3452
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis of abnormal DNA methylation in muscle samples from monozygotic twins discordant for type 2 diabetes

Abstract: Abstract. The present study aimed to examine the changes in DNA methylation of gene promoters associated with type 2 diabetes (T2D). The DNA methylation profile dataset GSE38291 was downloaded from the Gene Expression Omnibus database. A paired t-test was used to analyze differences in the DNA methylation of gene promoters between T2D and normal muscle samples. Gene Ontology (GO) enrichment analysis was performed using online tool, The Database for Annotation, Visualization and Integrated Discovery. Whole-Geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 34 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…In another study, when the DNA methylation profile dataset GSE38291, downloaded from the Gene Expression Omnibus database, was examined for changes in DNA methylation of gene promoters associated with T2D by GO analysis, a total of 38 genes (e.g., SIRT1 , N‐acetyltransferase 6 [ NAT6 ], phospholipase A2 group XIIB [ PLA2G12B ], and nuclear factor of activated T cells calcineurin‐dependent 1 [ NFATC1 ]) were identified to be differentially methylated between the muscles of T2D and control samples. Analysis of transcription factor binding sites for the methylation changes revealed that the binding sites of zinc finger E‐box binding homeobox 1 ( ZEB1 ) were hypermethylated, whereas the binding sites of three TFs (methyl CpG binding protein 2 [MECP2], TFEB, and TFAP4) were significantly hypomethylated 129 …”
Section: Dna Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, when the DNA methylation profile dataset GSE38291, downloaded from the Gene Expression Omnibus database, was examined for changes in DNA methylation of gene promoters associated with T2D by GO analysis, a total of 38 genes (e.g., SIRT1 , N‐acetyltransferase 6 [ NAT6 ], phospholipase A2 group XIIB [ PLA2G12B ], and nuclear factor of activated T cells calcineurin‐dependent 1 [ NFATC1 ]) were identified to be differentially methylated between the muscles of T2D and control samples. Analysis of transcription factor binding sites for the methylation changes revealed that the binding sites of zinc finger E‐box binding homeobox 1 ( ZEB1 ) were hypermethylated, whereas the binding sites of three TFs (methyl CpG binding protein 2 [MECP2], TFEB, and TFAP4) were significantly hypomethylated 129 …”
Section: Dna Methylationmentioning
confidence: 99%
“…Analysis of transcription factor binding sites for the methylation changes revealed that the binding sites of zinc finger E‐box binding homeobox 1 ( ZEB1 ) were hypermethylated, whereas the binding sites of three TFs (methyl CpG binding protein 2 [MECP2], TFEB, and TFAP4) were significantly hypomethylated. 129 …”
Section: Dna Methylationmentioning
confidence: 99%
“…Epigenetics describes a number of biological processes whereby gene expression is regulated and maintained through cell division and includes the addition of small mole cules such as the methyl group (CH 3 ) to DNA and its packaging proteins. Recently, epigenetic analyses of disease-discordant MZ twins have drawn attention to mechanisms relevant to the differential expression of relevant genes [5,6], barring the presence of rare postzygotic mutation [7]. DNA methylation at the dinucleotide CpG is an epigenetic mechanism which is often associated with repression of gene expression.…”
Section: Introductionmentioning
confidence: 99%